YOUTH COMMUNICATION CAMPAIGN IN STRENGTHENING DIFABELS THROUGH ICT-BASED PHILANTHROPY - Yuliana Rakhmawati; Rizki Ernaldi (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2020)
Ableism is a differentiation construction often experienced by entities with disabilities and contributes to discrimination in the fulfillment of personal, economic, and social rights for persons with disabilities. Designfordream (dfd) presents a form of youth awareness that concerns about philanthropic communication innovation strategies on ableism. This study aims to describe Designfordream's communication strategy in delivering communication through philanthropic activities. This study used a qualitative descriptive method. The data collection observed the Designfordream philanthropic activities through interviews with management and makes some documentation for the relevant sources. The results showed that the communication strategy used by Designfordream was through an ICT-based communication campaign. This campaign is carried out by distributing anti-ableism messages and innovating in building market networks to strengthen people with disabilities' entrepreneurial capacity.